Narrative review of relationship between chronic cough and laryngopharyngeal reflux - Hránková, Viktória; Balner, Tomáš; Gubová, Patrícia; Staníková, Lucia; Zeleník, Karol; Komínek, Pavel (Frontiers in Medicine, 2024)
Gastroesophageal reflux disease (GERD) as a possible cause of chronic cough is known for decades. However, more than 75% of patients with extraoesophageal symptoms do not suffer from typical symptoms of GERD like pyrosis and regurgitations and have negative upper gastrointestinal endoscopy. For such a condition term laryngopharyngeal reflux (LPR) was introduced and is used for more than two decades. Since the comprehensive information on relationship between chronic cough and LPR is missing the aim of this paper is to summarize current knowledge based on review of published information during last 13 years. Laryngopharyngeal reflux is found in 20% of patients with chronic cough. The main and recognized diagnostic method for LPR is 24-hour multichannel intraluminal impedance-pH (MII-pH) monitoring, revealing reflux episodes irritating the upper and lower respiratory tract mucosa. The treatment of LPR should be initiated with dietary and lifestyle measures, followed by proton pump inhibitor (PPI) therapy and other measures. Despite progress, more research is needed for accurate diagnosis and targeted therapies. Key areas for exploration include biomarkers for diagnosis, the impact of non-acid reflux on symptom development, and the efficacy of new drugs. Further studies with a focused population, excluding other causes like asthma, and using new diagnostic criteria for LPR are essential. It's crucial to consider LPR as a potential cause of unexplained chronic cough and to approach diagnosis and treatment with a multidisciplinary perspective.